AN ANALYSIS OF STUDENTS PERCEPTION OF THE USE OF ENGLISH IN BILINGUAL CLASS AT EIGHT GRADE OF SMP N 1 TEMBILAHAN - Salmiati; Nur Azzahra Diyanah Faizah; Samsul Amri (J-Shelves of Indragiri (JSI), 2024)
This paper discusses students perception on the use of English in bilingual class at eight grade of SMPN 1 Tembilahan. Knowing students’ perception is important for the teacher to know students learning outcomes what are their perceptions and what are the factors that affecting their perception because students' perceptions of learning outcomes can provide valuable insights into their understanding, satisfaction, and engagement with the educational process. The purpose of this research was to determine what are students perceptions on the use of English in the bilingual class and also to determine what are the factors affecting of the students perception on the use of English in Bilingual Class at Eight Grade of SMP N 1 Tembilahan. This research was a quantitative descriptive research. This research instrument used a questionnaire which contains 25 statements. The total population was 60 students, and the total sample was 31 students. The sampling technique in this research was purposive sampling, the sample used in this research was the eight grade students of bilingual class at SMPN1 Tembilahan. Furthermore, based on the results of calculating students response to 25questionnaire statements, it was found that the students perception on the use of English in the bilingual class at Eight grade SMPN 1 Tembilahan is in very good level. It can be interpreted that, most of Eight grade students of bilingual class of SMP N 1 Tembilahan already have a very good point of view on the use of English in bilingual class and the factors that more influence the results of students' perceptions of the use of English in bilingual class are internal factors. This is because internal factors have more dominant results compared to external factors. So, it can be concluded that eighth grade bilingual students of SMPN 1 Tembilahan have a very good perception of the use of English during the learning process.